2014
DOI: 10.1016/j.jcol.2014.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Management of acute colorectal diseases in febrile neutropenic patients

Abstract: Patients with hematologic malignancies are susceptible to serious complications due to immunosuppression. Neutropenic-related infection is one of the major causes of morbidity and mortality in this group of diseases. Febrile neutropenia is a common complication of the hematologic neoplasm itself or chemotherapy, and has worse prognosis if prolonged (lasting more than 7 days) or severe (neutrophil count below 500 cells per μL). Among the usual sites of infection, we highlight the neutropenic enterocolitis and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Manifestations of perianal infections may differ from those with a competent immune system 3 and are often accompanied by severe pain, swelling, constipation, and may cause systemic infection. 6 However, the clinical presentation of an anorectal infection is often masked by the absence of inflammatory cells so recognition of the signs and symptoms can be difficult in neutropenic patients.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Manifestations of perianal infections may differ from those with a competent immune system 3 and are often accompanied by severe pain, swelling, constipation, and may cause systemic infection. 6 However, the clinical presentation of an anorectal infection is often masked by the absence of inflammatory cells so recognition of the signs and symptoms can be difficult in neutropenic patients.…”
Section: Discussionmentioning
confidence: 99%
“… 7 Perianal infections are a life-threatening complication including Fournier’s gangrene that requires rapid diagnosis and intervention as recurrence and mortality rates may be expressive. 3 , 8 In a series of 92 patients with acute or chronic leukemia, most common manifestations were a perirectal abscess (27%) followed by anal fissures (23%), external hemorrhoids (19%) and perianal ulcerations (13%). 3 Another retrospective study found a perianal infection prevalence of 6.7% and recurrence was diagnosed in 31% of the cases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations